Canon, print, and the Virgilian corpus. (29th January 2018) - Kallendorf, Craig
Abstract: This essay shows how the early printed editions of Virgil both reflect and shape the place of the poet's minor works in the canon of classical authors in the Renaissance. These editions of the Opuscula demonstrate that early modern readers encountered as many as sixty shorter works rather than just those found in the Appendix Virgiliana . Most early readers considered these poems Virgilian, primarily because they were compatible with their interpretation of Virgil's major works, which were generally understood to praise virtue and condemn vice in accordance with the principles of epideictic rhetoric. As early modern readers sought to understand the Opuscula through this lens, however, tensions arose, especially around the Priapea, which could not be integrated within the epideictic versions of the longer poems. These tensions played out in the pages of the early books, where incompatible elements jostled against one another and offending material ultimately lost out to censorship. By 1650 most of the minor works were no longer included in the Virgilian canon, as it was represented in the printed editions of that time. The essay concludes with some reflections on how attention to the material form of texts can enrich the practice of reception in general.